2015
DOI: 10.1111/acer.12900
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Protects Mice Against Acute Alcohol‐Induced Liver Injury

Abstract: Background Chronic alcohol abuse is associated with intestinal bacterial overgrowth, increased intestinal permeability, and translocation of microbial products from the intestine to the portal circulation and liver. Translocated microbial products contribute to experimental alcoholic liver disease. Aim To investigate the physiological relevance of the intestinal microbiota in alcohol-induced liver injury. Methods We subjected germ-free and conventional C57BL/6 mice to a model of acute alcohol exposure that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 24 publications
5
87
0
Order By: Relevance
“…This fits with recently presented data where Chen et al 57 showed that ALD is aggravated in germ-free mice and in these studies hepatic ethyl alcohol (EtOH) metabolism was enhanced and susceptibility to binge-like alcohol drinking increased. Another exciting research area deals with the key questions how an intact intestinal microbiota is regulated.…”
Section: Alcoholic Liver Disease and Microbiotasupporting
confidence: 92%
“…This fits with recently presented data where Chen et al 57 showed that ALD is aggravated in germ-free mice and in these studies hepatic ethyl alcohol (EtOH) metabolism was enhanced and susceptibility to binge-like alcohol drinking increased. Another exciting research area deals with the key questions how an intact intestinal microbiota is regulated.…”
Section: Alcoholic Liver Disease and Microbiotasupporting
confidence: 92%
“…Rodents have also been shown to have increased endotoxemia after binge consumption of ethanol 40 . Interestingly, germ-free mice given an alcohol gavage developed more severe acute alcohol-associated injury than mice with a control microbiome 41 .…”
Section: Role For the Intestinal Microbiotamentioning
confidence: 99%
“…To test the roles of gut microbiota in the pathogenesis of acute ALD, the sensitivity to binge drinking (3 g/kg body weight)-induced liver injury was compared between germ-free and conventional C57BL/6 mice (118). Unexpectedly, germ-free mice were found to be more susceptible to binge drinking-induced hepatic fat accumulation, elevation of serum aminotransferase activity, and hepatic inflammation compared with the conventional mice.…”
Section: Roles Of Kcs In Acute Ethanol/binge Drinking-induced Liver Imentioning
confidence: 99%